RANCANG BANGUN SISTEM INFORMASI PENJUALAN DAN SERVICE MOTOR BERBASIS WEB DENGAN METODE PROTOTYPE PADA BENGKEL MAJU JAYA MOTOR - Linawati, Safitri; Nurdiani, Siti; Nugraha, Wahyu; Rezki, Muhammad; Saputra, Dicky (Jurnal Sistem Informasi Akuntansi, 2023)
Maju Jaya Motor Workshop still uses physical structures such as for sales and service. Therefore making sales reports and motorbike service reports takes time to make these reports. Sometimes insufficient stock makes selling difficult because reports have to be checked manually. After that, they buy the product. So it's not real-time because it's still being checked and then bought. Therefore the author created a web-based system design to facilitate sales and display inventory at the Maju Jaya Motor workshop. The steps of the system development method used in this study are Communication, Planning, Modeling, Construction and Delivery. The proposed solution to this problem was expected with an app I built because it removes the need to manually check inventory, making buying parts there more reasonable. There is no need to do physical records when selling and servicing motorbikes because if the system already exists, it can be printed on the system and there is no need to summarize sales and service reports anymore.